Research of Internal Excitation of Helical Gear Meshing Transmission - Yue Huijun; Song Yuanyuan; Liu Yang; Xu Xiangyang (Jixie chuandong)
The internal excitation of gear meshing transmission is the key factor that causes gear vibration and noise. Taking a pair of constant meshing helical gears in an 8-speed automatic transmission as the research object,the internal excitation of meshing transmission process is studied thoroughly,including the tooth surface contact state,time-varying meshing stiffness,error excitation and meshing impact. The finite element method is used to analyze the static and dynamic contact process of helical gears to get the magnitude and distribution of tooth contact stress. The change of contact line length is used to represent the time-varying meshing stiffness. The time-varying meshing stiffness of helical gear is obtained by theoretical analysis and finite-element simulation. Theoretical analysis and finite-element method are used to analyze the error excitation of helical gears,including the meshing error,the static transmission error and the dynamic transmission error. The finite-element method is used to analyze the meshing impact to obtain the root stress of gear transmission. The stress distribution on tooth contact line is calculated by the finite-element method. The above research lays the foundation for the improvement of helical gear transmission state.